A calibration methodology to obtain material parameters for the representation of fracture mechanics based on discrete element simulations. (January 2017) - Behraftar, S.; Galindo Torres, S.A.; Scheuermann, A.; Williams, D.J.; Marques, E.A.G.; Janjani Avarzaman, H.
Abstract: A micro-mechanical model is developed to study the fracture propagation process in rocks. The model is represented by an array of bonded particles simulated by the discrete based method. Experimental results of tests using Cracked Chevron Notched Brazilian Discs (CCNBD) with different inclination angles relative to the direction of loading are used to calibrate and validate the model. Dimensional analysis is used to identify and minimise the microscale parameters to be considered. The comparison between experimental and computational results shows a satisfactorily good agreement.